Misunderstandings in ATC Communication : Language, Cognition, and Experimental Methodology. - Barshi, Immanuel (Ashgate studies in human factors for flight operations., 2016)
Effective radio communication between ATC and pilots has long been recognized as an important element of aviation safety. In recognition of the role miscommunications play in aviation incidents and accidents, the International Civil Aviation Organization (ICAO) recently introduced language proficiency requirements for all flight personnel in all ICAO member states. Using an effective and economical experimental paradigm, the research described here teases apart the complex combination of factors (e.g. speech rate, controller message length, English language proficiency, cognitive workload) bel.